2021
DOI: 10.3390/ijms22063129
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterisation of Three Glycine N-Acyltransferase Variants and the Effect on Glycine Conjugation to Benzoyl–CoA

Abstract: The glycine conjugation pathway in humans is involved in the metabolism of natural substrates and the detoxification of xenobiotics. The interactions between the various substrates in this pathway and their competition for the pathway enzymes are currently unknown. The pathway consists of a mitochondrial xenobiotic/medium-chain fatty acid: coenzyme A (CoA) ligase (ACSM2B) and glycine N-acyltransferase (GLYAT). The catalytic mechanism and substrate specificity of both of these enzymes have not been thoroughly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 85 publications
(128 reference statements)
2
25
0
Order By: Relevance
“…Distribution of sequence variation allowed characterization of four different alleles in addition to the reference allele. Due to the suspicious high allele frequency of c.467A>G, this variant may have been regarded as the real GLYAT wild-type [101], which has been corroborated by enormous high enzyme activity of p.(Asn156Ser) variant [129,152,154]. thioredoxin and glutaredoxin system that reduce disulfide bonds in bacteria cytoplasm, thus destroying tertiary protein structure [124].…”
Section: Identification Of Human Glyat Polymorphisms In the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Distribution of sequence variation allowed characterization of four different alleles in addition to the reference allele. Due to the suspicious high allele frequency of c.467A>G, this variant may have been regarded as the real GLYAT wild-type [101], which has been corroborated by enormous high enzyme activity of p.(Asn156Ser) variant [129,152,154]. thioredoxin and glutaredoxin system that reduce disulfide bonds in bacteria cytoplasm, thus destroying tertiary protein structure [124].…”
Section: Identification Of Human Glyat Polymorphisms In the Literaturementioning
confidence: 99%
“…Those, in combination with co-expressed GroES/GroEL [17], the Trx-tag fusion [33] and the compatible pET32 plasmid system [174] cover the certain compulsory requirements for the overexpression of eukaryotic GLYAT in a prokaryotic system. It has been used several times for the overexpression of GLYAT [129,152,154]. On the other side, mutations within these genes resulted in a decreased growing rate of E. coli Origami 2(DE3) in contrast to other E. coli strains [22,124] -a problematic challenge within the project, which will be described more precisely (Section 4.4.).…”
Section: Identification Of Human Glyat Polymorphisms In the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Due to its physiological relevance, human GLYAT has recently received considerable attention. Many groups have reported genetic polymorphisms in the GLYAT gene, and in vitro studies of the prevalent variants showed some of the mutations affect enzymatic activity [8][9][10][11] (Supplementary Table 2). Without a representative GLYAT structure, previous analyses were based on homology models generated using low identity templates (<12 %) 8 , which could introduce severe bias.…”
Section: (E227q)mentioning
confidence: 99%